The Cultural Memory of Protest - Knittel, Suzanne C. (Incontri. Rivista europea di studi italiani, 2014)
Review of Andrea Hajek, Negotiating Memories of Protest in Western Europe. The Case of Italy, Basingstoke, Palgrave Macmillan, 2013, 232 p., ISBN: 9781137263773, € 64,00.